Clarification and Refinement of Modernization Theory: How the Global Economy Impacts Homicide Rates. Issue 4 (2nd October 2019) - Levchak, Philip J.
ABSTRACT: Studies of homicide that utilize modernization theory to explain cross-national variation suffer from a major shortcoming. Namely, they neglect the way in which nations currently develop. As a result, the purpose of this theoretical piece is twofold. First, it outlines the development of modernization theory by Emile Durkheim and its refinement by subsequent scholars. Second, it discusses the weaknesses of modernization theory and presents a rationale for why scholars should consider how various measures of globalization can impact rates of homicide. A large body of literature finds that such measures produce economic growth, urbanization, and inequality. These three outcomes are key covariates within the modernization tradition.